Summer annual forages in south central Kansas - Blasi, Dale A.; Fjell, Dale L.; Shroyer, James P.; Kuhl, Gerry L.; Heer, William F. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Six, summer annual forages and three forage sorghums were evaluated for forage yield and quality under south central Kansas dryland conditions. The sudans and forage sorghums produced similar amounts of dry matter per acre, and yields for these two forage types were significantly higher than for the pearl millet cultivars tested. Conversely, the pearl millets provided higher quality forage in terms of crude protein and acid detergent fiber levels. Droughty conditions severely limited forage yields. However, forage nitrate and prussic acid levels were all relatively low, indicating the utility of raising the cutter bar to avoid harvesting the lower stalks that can contain high nitrate concentrations.
Keywords: Beef; Summer annuals; Forage sorghums; Yield; Forage quality; Nitrate